THE EFFECT OF PROVIDING REPRODUCTIVE HEALTH VIDEO MEDIA ON ADOLESCENT BEHAVIOR AT SD INPRES BAKUNG 1 MAKASSAR CITY IN 2022 - Jumini, Jumini; Multazam, Muhammad; Nurlinda, Andi (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effect of providing reproductive health video media on adolescent behavior at SD Inpres Bakung 1 Makassar City. This type of research is quantitative analytic research using a quasi-experimental approach. The research design is two groups pretest-posttest. The population in this study were all students at SD Inpres Bakung 1 Makassar City, and a sample of 74 people was divided into two groups, namely 37 people in the intervention group and 37 people in the control group. The sampling technique used inclusion and exclusion criteria. The data collection technique was through direct interviews using a questionnaire. This research was conducted from March to April 2022. Data analysis used the Mann-Whithney statistical test. The results showed that there was a significant effect of video media on student knowledge with a p-value of 0.011, there was no significant effect of video media on student attitudes with a p-value of 0.102, and there was no significant effect of video media on student behavior with a p-value of 0.180. The results showed that there was a significant effect of 2x video media on students' knowledge with a p-value of 0.000, there was a significant effect of 2x video media on students' attitudes with a p-value of 0.000, there was a significant effect of video media on student behavior with a p-value of 0.005. It was concluded that students must maintain and improve their behavior regarding reproductive health. It is hoped that future research will use different media to measure adolescent behaviour regarding reproductive health.